Tax evasion and money laundering - an open and shut case - Bridges, Martyn J. (Informal Economy Research Centre LondonGB, 2000)
Focuses on the application of the money laundering legislation to the proceeds of domestic and foreign tax evasion. Looks at the practical implications if the proceeds of domestic and foreign tax evasion are coverd by the money laundering legislation. Includes the UK government's position.